Persepsi Keluarga Penerima Bantuan Iuran Terhadap Kebijakan BPJS Kesehatan: (Kasus Keluarga Penerima Bantuan Iuran BPJS Kesehatan Di Desa Cileunyi Wetan Kecamatan Cileunyi Kabupaten Bandung) - Yahya, Shopi Naziihah; Favourita, Lina; Heryana, Wawan (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2021)
Perception is the process of recognizing an object using by the five senses in the form of knowledge, experience of an object and then provide an assessment to the object. Perception of recipient of contribution assistance family to social security agency (BPJS) health policies in Cileunyi Village Cileunyi Wetan District of Bandung Regency refers to three aspects 1) knowledge 2) assessment and 3) experience to be studied. The method in this research is quantitative method, using simple random sampling technique to 78 respondents from recipient of contribution assistance. Data collection techniques using questionnaire, documentation and observation studies. The test of measuring instrument validity using the face validity and reliability test using Cronbach alpha. The analysis of data using Microsoft Excel and SPSS. The results was showed an aspect of the high category that aspect of the experience aspect and the other two aspects show enough or medium category, but one of them has the lowest actual score that is the knowledge aspect. The average value obtained from all aspects with the actual score 244.16 from the ideal score 312. The proposed program is the socialization of the service guide and rules for participants BPJS to improve knowledge of recipient of contribution assistance family in the Cileunyi Wetan Village Cileunyi District of Bandung Regency and using Community Organization and Community Development Organization (COCD) method with a campaign technique.